2008
DOI: 10.1093/cvr/cvn288
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular adipose tissue-derived visfatin is a vascular smooth muscle cell growth factor: role of nicotinamide mononucleotide

Abstract: Visfatin stimulates VSMC proliferation via NMN-mediated ERK1/2 and p38 signalling. The present study provides a molecular link of visfatin to the paracrine action of PVAT, demonstrates a novel function of visfatin in promoting VSMC proliferation, and reveals NMN as a novel signalling molecule that triggers the proliferative process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
248
4
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(271 citation statements)
references
References 26 publications
14
248
4
5
Order By: Relevance
“…In line with our observations, Wang et al have recently reported that exogenous NMN, at the same concentration used in this study, mimics the proliferative action of ePBEF/NAMPT/visfatin in rat vascular smooth muscle [18]. Here, we demonstrate that extracellular NMN can also be considered as a proinflammatory agent for human vascular smooth muscle.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our observations, Wang et al have recently reported that exogenous NMN, at the same concentration used in this study, mimics the proliferative action of ePBEF/NAMPT/visfatin in rat vascular smooth muscle [18]. Here, we demonstrate that extracellular NMN can also be considered as a proinflammatory agent for human vascular smooth muscle.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, other cellular effects triggered by ePBEF/NAMPT/visfatin, including the secretion of IL-8 and TNF-α by human peripheral blood mononuclear cells [23] and the uptake of glucose in rat mesangial cells [27], also seem to involve the insulin receptor. Other studies, however, have discarded a role for this receptor in mediating the actions of ePBEF/NAMPT/ visfatin in a wide range of cell types, including vascular cells, macrophages and pancreatic beta cells [11,14,18,28]. The results presented herein do not support a role for the insulin receptor in mediating the pro-inflammatory action of ePBEF/NAMPT/visfatin in human vascular smooth muscle cells.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Revollo et al (11) have demonstrated that visfatin regulates insulin secretion in pancreatic β-cells through its intrinsic NAMPT enzymatic activity. Wang et al (27) have reported that visfatin stimulates vascular smooth muscle cell proliferation via the NMN-mediated ERK1/2 and p38 signaling. In a recent study, Romacho et al (10) have shown that NAMPT activity is involved in visfatin's pro-inflammatory action in smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Human osteosarcoma cell lines (Saos-2, U-2OS and MG-63), human malignant melanoma cell line A375 and human osteoblast cell line Hob were obtained from the American Type Culture Collection (ATCC; Manassas, VA, USA) and cultured in Iscove's modified Dulbecco's medium (IMDM; Invitrogen, Carlsbad, CA, USA), supplemented with 20 U/ml penicillin, 100 µg/ml streptomycin (Sigma, Beijing, China), and 10% heat-inactivated fetal bovine serum (FBS; Biowhittaker, Walkersville, MD, USA) at 37˚C in a humidified incubator supplied with 5% CO 2 (25).…”
Section: Methodsmentioning
confidence: 99%